2016
DOI: 10.1515/saeb-2016-0105
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Rules for Computing Corporate Income Tax on the Accuracy of Financial Statements of Lithuanian Companies

Abstract: Companies in Lithuania have to follow Business Accounting Standards (BAS) when

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The useful life for the same type of asset may vary from several years to tens of years. Companies of accelerated depreciation methods and failure to revalue assets so that they reflect true asset value (Cernius et al 2016). As a result, the value of long-term assets recorded in the balance sheet is understated, thus making the company's financial situation look worse than it is.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The useful life for the same type of asset may vary from several years to tens of years. Companies of accelerated depreciation methods and failure to revalue assets so that they reflect true asset value (Cernius et al 2016). As a result, the value of long-term assets recorded in the balance sheet is understated, thus making the company's financial situation look worse than it is.…”
Section: Introductionmentioning
confidence: 99%
“…However, even in the context of large companies, there's evidence that such distortions exist. Prior research revealed that companies were using considerable capacities of fully depreciated long-term assets (Cernius et al 2016).…”
Section: Introductionmentioning
confidence: 99%